KINERJA PEMERINTAH DESA DALAM PENYELENGGARAAN DIGITALISASI DESA DI DESA PETUMBUKAN KECAMATAN GALANG KABUPATEN DELI SERDANG - Pangaribuan, Nur Ajijah; Batubara, Beby Mashito; Deliana, Marlina (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This paper aims to see how village digitalization can accelerate village performance in Petumbukan village. The method used in this paper is a descriptive method with a qualitative approach. The results of this study indicate that the ongoing digitalization in Petumbukan village has a positive impact in terms of providing improvements to services to village communities.